Immobilization of enzymes and cells (Methods in biotechnology, 1997)
Gordon Bickerstaff offers in Immobilization of Enzymes and Cells today's most representative collection of time-tested immobilization procedures and methods now so widely used in both industrial and research laboratories. These unfailingly reproducible techniques are so crafted that users can easily incorporate them into their existing methods and processes. Extensive notes provide additional information that help extend the flexibility of the method. Immobilization of Enzymes and Cells is an indispensable tool for all academic and industrial research workers seeking to introduce or to expand the use of immobilization techniques in their work. It will enable senior researchers, as well as those new to these procedures, quickly to master the powerful methodology of enzyme and cell immobilization.